2017
DOI: 10.15405/epsbs.2017.10.36
|View full text |Cite
|
Sign up to set email alerts
|

Learning Patterns Of Czech And Romanian Students Within The Context Of An Crosscultural Comparison

Abstract: International comparison represents useful perspective on academic learning in today's globalized world. Eastern European countries however so far have not figured in international comparisons of higher education much. The aim of the study was to fill an empty space on an imaginary map of academic learning and add results of students from two countries of the former Communist bloc, to gain new understanding of the current state of learning of university students from different countries and indicate impulses f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Our study confirmed the fact that for the theoretical and individual subject matters the online teaching and learning methods could be more efficient and more appropriate for music education than for individual subject matters, the first hypothesis being supported by the data obtained. Therefore, teachers could consider using e-learning platforms for theoretical subject matters in music education as an opportunity for increased musical exchange and cultural interaction (Juklová et al, 2017;Cho, 2021). The low perceived efficiency for group subjects could be explained by the fact that the online context limits the interpersonal experiences leading to a sense of loss of social connections due to the lack of socializing opportunities and joint music-making (Levstek et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed the fact that for the theoretical and individual subject matters the online teaching and learning methods could be more efficient and more appropriate for music education than for individual subject matters, the first hypothesis being supported by the data obtained. Therefore, teachers could consider using e-learning platforms for theoretical subject matters in music education as an opportunity for increased musical exchange and cultural interaction (Juklová et al, 2017;Cho, 2021). The low perceived efficiency for group subjects could be explained by the fact that the online context limits the interpersonal experiences leading to a sense of loss of social connections due to the lack of socializing opportunities and joint music-making (Levstek et al, 2021).…”
Section: Discussionmentioning
confidence: 99%